Once upon a tartan eaudiobook - Burrowes, Grace (MacGregors, 2013)
Tiberius Flynn travels to Scotland with orders to snatch his young niece away from her Highland relations. He thinks it's going to be an easy task, until he meets the feisty little girl and her fiercely protective step-aunt. A smart, headstrong beauty, Hester Daniels has no use for an English lord with high-handed ways, no matter how handsome or beguiling he may be. Tye sets out to seduce Hester and win over Fiona, only to discover that he's losing his heart to a woman who's as untamable as Scotland itself.